Acyl-CoA-dependent and acyl-CoA-independent avocado acyltransferases positively influence oleic acid content in nonseed triacylglycerols - Behera, Jyoti; Rahman, Md Mahbubur; Shockey, Jay; Kilaru, Aruna (Frontiers in Plant Science, 2023)
In higher plants, acyl-CoA:diacylglycerol acyltransferase (DGAT) and phospholipid:diacylglycerol acyltransferase (PDAT) catalyze the terminal step of triacylglycerol (TAG) synthesis in acyl-CoA-dependent and -independent pathways, respectively. Avocado (Persea americana) mesocarp, a nonseed tissue, accumulates significant amounts of TAG (~70% by dry weight) that is rich in heart-healthy oleic acid (18:1). The oil accumulation stages of avocado mesocarp development coincide with high expression levels for type-1 DGAT (DGAT1) and PDAT1, although type-2 DGAT (DGAT2) expression remains low. The strong preference for oleic acid demonstrated by the avocado mesocarp TAG biosynthetic machinery represents lucrative biotechnological opportunities, yet functional characterization of these three acyltransferases has not been explored to date. We expressed avocado PaDGAT1, PaDGAT2, and PaPDAT1 in bakers’ yeast and leaves of Nicotiana benthamiana. PaDGAT1 complemented the TAG biosynthesis deficiency in the quadruple mutant yeast strain H1246, and substantially elevated total cellular lipid content. In vitro enzyme assays showed that PaDGAT1 prefers oleic acid compared to palmitic acid (16:0). Both PaDGAT1 and PaPDAT1 increased the lipid content and elevated oleic acid levels when expressed independently or together, transiently in N. benthamiana leaves. These results indicate that PaDGAT1 and PaPDAT1 prefer oleate-containing substrates, and their coordinated expression likely contributes to sustained TAG synthesis that is enriched in oleic acid. This study establishes a knowledge base for future metabolic engineering studies focused on exploitation of the biochemical properties of PaDGAT1 and PaPDAT1.